Pengaruh Kualitas Pelayanan Perpustakaan Digital terhadap Peningkatan Minat Baca Mahasiswa pada Dinas Perpustakaan Daerah Kota Medan - Sri Ramadani; Franindya Purwaningtyas (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This research was aimed to examine empirically the effect of service quality digital library on Reading interest. The analysis used an independent variable (Quality Service Digital Library) and dependent variable (Reading Interest). The sample was conducted by purposive sampling method. This study location at perpustakaan PEMKO Medan Jalan Iskandar Muda Collecting data was conducted by a questionnaire distributed directly to responden and visitor as much 30 questionnaires. The statistical method used was multiplied analysis linear regression, with hypotheses testing of statistic t-tests. The result of this research showed that There is a significant positive influence between the quality of digital library services on students' reading interest in the regional library of Medan City (Library and Archives Service). Obtained based on the significance value that by partial test the significance value of t is 0.001 < than 0.05 this value shows the t value is smaller than the significance value of 0.05.